Seleção de matrizes e avaliação de características associadas ao vigor de Dipteryx alata Vogel - Pereira, Brenda Gillian (Universidade Federal de São Carlos, 2026)
Initial seedling vigor is an important tool for evaluating seed physiological quality and selecting promising materials in native forest species. In this context, the objective of this study was to evaluate germination traits and initial seedling vigor of Dipteryx alata derived from mother trees with different diameter at breast height (DBH) values. The material was obtained from an experimental plantation located in Pederneiras, São Paulo, using seeds collected from ten mother trees. Physical and sanitary analyses of the seeds were performed, as well as daily evaluations of germination, emergence, and initial seedling growth. Parameters related to germination dynamics, morphological growth, and dry biomass production were also estimated. The results showed differences among treatments in germination speed, initial growth, and biomass accumulation, indicating variability in physiological vigor among the evaluated mother trees. Some treatments exhibited faster germination and better performance in shoot growth, root system development, and biomass production. However, no consistent association was observed between seedling performance and the DBH values of the mother trees. It was concluded that the evaluated traits were efficient in distinguishing materials regarding physiological vigor during the initial stages of development, although DBH alone was not a consistent indicator of progeny performance under the evaluated conditions.
Selection of parent stock and evaluation of characteristics associated with the vigor of Dipteryx alata Vogel
Keywords: Qualidade fisiológica; Forest breeding; Genetic parameters; Germination; Early development; Cerrado species; Germinação; Crescimento de plântulas; Desempenho germinativo; Biomassa; Melhoramento florestal; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; 12. Consumo e Produção Responsáveis; 15. Vida Terrestre